Proceedings of the 38th International Conference on Software Engineering Companion 2016
DOI: 10.1145/2889160.2889182
|View full text |Cite
|
Sign up to set email alerts
|

How surveys, tutors, and software help to assess Scrum adoption in a classroom software engineering project

Abstract: Agile methods are best taught in a hands-on fashion in realistic projects. The main challenge in doing so is to assess whether students apply the methods correctly without requiring complete supervision throughout the entire project.This paper presents experiences from a classroom project where 38 students developed a single system using a scaled version of Scrum. Surveys helped us to identify which elements of Scrum correlated most with student satisfaction or posed the biggest challenges. These insights were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Combining an established taxonomy with a field study, we selected three processes to augment a course design, and showed evidence that these additions improve learning outcomes without interfering with prior processes. Teaching and measuring team processes is difficult [8,22], but using tools that generate instructor-visible data, as we have done, can provide better insights into student behaviors. In the future we hope to use this data to determine whether teams that adhere more closely to the processes experience better learning outcomes, produce higher quality software artifacts, or both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining an established taxonomy with a field study, we selected three processes to augment a course design, and showed evidence that these additions improve learning outcomes without interfering with prior processes. Teaching and measuring team processes is difficult [8,22], but using tools that generate instructor-visible data, as we have done, can provide better insights into student behaviors. In the future we hope to use this data to determine whether teams that adhere more closely to the processes experience better learning outcomes, produce higher quality software artifacts, or both.…”
Section: Resultsmentioning
confidence: 99%
“…Our self-assessment surveys and checkpoints measure self-efficacy, so we use them as reasonable proxy measurements for learning outcomes. Previous studies have also shown that surveys are useful instruments for teaching software engineering processes [22].…”
Section: Data Collectionmentioning
confidence: 99%
“…At the beginning of the project, the team's Product Owners need to work together to create initial user stories for the first development sprint from interviews with the product customer. While they are guided by extensive tutoring, our experience has shown that this task of collaboration in combination with new tasks is challenging for students [54]. As a result, the distribution of responsibilities and user stories between teams can lead to duplications of user stories.…”
Section: E Survey Discussionmentioning
confidence: 99%
“…Previous studies have explored the use of metrics in teaching software engineering courses [11] [12]. Matthies et al further summarized their metrics into a system called ScrumLint [13].…”
Section: Metricsmentioning
confidence: 99%